Research trends in carbon capture and storage: A comparison of China with Canada. (June 2020) - Wang, Jin-Wei; Kang, Jia-Ning; Liu, Lan-Cui; Nistor, Ioan; Wei, Yi-Ming
Highlights: Cumulative publication of China's CCS research was about 3.4 times that of Canada. China's CCS research had the advantage of pre-combustion carbon capture. Canada's CCS research advantage lied in the ecosystem carbon sequestration. Canada's CCS research will reach saturation 15 years later than that in China. Abstract: In order to effectively address climate change, academia and industry have paid much attention to the development trend of Carbon Capture and Storage (CCS). However, there is no mature CCS research trend monitoring system. China is likely to be the largest market for CCS technology in the future, while Canada is the first country to start the research and development of CCS. Existing studies have discussed the CCS research trends at the global level, in China, Canada, and in other countries. However, few comparative studies have been carried out in key countries. In this study, an integrated method of bibliometrics and S-Curve is proposed with the purpose of comparing CCS research trends between China and Canada. Firstly, the bibliometrics method was used to compare the conceptual structure and research route of CCS research in China and in Canada. Secondly, the key collaborators were indentified through the comparison of collaboration relationships. Finally, the S-Curve model was employed to forecast the CCS research output trend in China and Canada. This study found that China's CCS research had the advantage of pre-combustion carbon capture, while Canada's advantage lied in the ecosystem carbon sequestration. It was also shown that Canada's CCS cumulative publication may reach saturation 15 years later than that in China. This paper provides insight into the CCS research and development optimization for China, Canada and globally. The CCS research trends comparison tools proposed in this study can benefit to monitor the CCS research by governments and enterprises.